Perkecambahan Benih Aren (Arenga Pinnata) Setelah Diskarifikasi Dengan Giberelin Pada Berbagai Konsentrasi - Oktoviani Purba; Indriyanto .; Afif Bintoro (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Dormancy of sugar palm seed (Arenga pinnata) was caused of hard seed coat structure, making its difficult to absorb water during of germinating. Dormancy in seed can be resolved by giving of treatmeant physically, mechanically, or chemically. This research aimed to determine the effect of physical treatment and chemical treatment on the germination of sugar palm seeds and determine which affect gibberellin concentration most favorable to the germination of sugar palm seeds. In this research, dormancy in seed be resolved in chemically that way with soaking of water with temperature early 75 0 C let to be chilled during 15 minute, and then soaking in condensation of giberelin with concentration of giberellins is 0 ppm, 50 ppm, 100 ppm, 150 ppm, and 200 ppm for 24 hours.Â The method used in this research is Complete Random Design (CRD) which consisting of five treatments and four replications. The results showed that the treatment accorded significant effect on germination percentage, germination, and the average days to germinate. Addition of soaking in a solution of 150 ppm giberellin for 24 hours gives the best effect with an average germination percentage by 65%, compared with addition of soaking in giberellin solution of 0 ppm, 50 ppm, 100 ppm, 200 ppm giberellins for 24 hours with an average germination percentage by 15%, 34,5%, 53,125%, and 26,875%.